Space Identity in Kronstadt: Analysis of Street and Food Services Names - N. A. Manzhina (Сравнительная политика, 2015)
Th is article is focused on space identity by analyzing informal sources such as the names of streets, cafes and restaurants. Th e research reveals unconscientious self-identifi cation of Kronstadt. Despite the fact that the town has the status of an opened city, it has not changed its self-perception as a separated territorial unit, distinct from others and secured from the contacts with the external world.